2020
DOI: 10.1101/2020.11.02.20222489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An evaluation of assumptions underlying respondent-driven sampling and the social contexts of sexual and gender minority youth participating in HIV clinical trials in the United States

Abstract: Introduction: Respondent-driven sampling has been an effective sampling strategy for HIV research in many settings, but has had limited success among some youth in the United States. We evaluated a modified RDS approach for sampling Black and Latinx sexual and gender minority youth (BLSGMY) and evaluates how lived experiences and social contexts of BLSGMY youth may impact traditional RDS assumptions. Methods: RDS was implemented in three cities to engage BLSGMY in HIV prevention or care intervention trials. R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…It was previously reported that some cases of asymptomatic and mildly symptomatic patients failed to mount neutralizing antibodies 1 – 4 , 9 , 10 . However, this study and other studies 5 , 7 , 12 , 22 indicate that by using current laboratory methods, the vast majority (> 95%) do developed detectable levels of IgM, IgG-S and IgG-N. Compared to the asymptomatic and the mild symptomatic cohorts, severe respiratory symptomatic patients generated two–fivefold higher antibody titers.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…It was previously reported that some cases of asymptomatic and mildly symptomatic patients failed to mount neutralizing antibodies 1 – 4 , 9 , 10 . However, this study and other studies 5 , 7 , 12 , 22 indicate that by using current laboratory methods, the vast majority (> 95%) do developed detectable levels of IgM, IgG-S and IgG-N. Compared to the asymptomatic and the mild symptomatic cohorts, severe respiratory symptomatic patients generated two–fivefold higher antibody titers.…”
Section: Discussioncontrasting
confidence: 47%
“…Since data in the early stages of the disease were gathered mostly from hospitalized patients or relatively late, after the onset of the infection 2 , 12 14 , there is a lack of knowledge about the early antibody kinetics in non-hospitalized patients with asymptomatic and mildly symptomatic disease. Moreover, the data regarding IgG levels against the spike (S) and nucleocapsid (N) antigens are based on blood samples collected at non-consequent timepoints 2 8 .…”
Section: Introductionmentioning
confidence: 99%
“…People with higher levels of stigma may fear outing to, and by their social networks, and may therefore decline participation when approached by members of their community. A recent analysis by Wirtz et al (2020) demonstrated that among same-gender loving youth in the United States, small social circles, limited peer trust, and HIV stigma may influence referrals in such studies (Wirtz et al, 2020). Additionally, sample size limited our ability to fully interrogate the impact of stigma on PrEP awareness and use by race.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited using respondent driven sampling (RDS). Targeted seed selection occurred using both direct and indirect seed selection [20]. Direct seed selection consisted of informational flyers directly given to a youth from study staff at a clinical site or at a community-based organization or in-person event (e.g., House Ball, Pride, community informational session).…”
Section: Methodsmentioning
confidence: 99%